Pengaruh Budaya Organisasi dan Loyalitas Karyawan Terhadap Kinerja Karyawan pada Firma Am Badar & Am Badar Jakarta Pusat - Mardi Muhamad; Cornelia Dumarya Manik (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study sought to ascertain, either partially or concurrently, the impact of organizational culture and employee loyalty on employee performance at Am Badar & Am Badar Firm, Central Jakarta. This study used a sample of 92 respondents and a quantitative methodology, in which all populations were used as sample material. Regression analysis, correlation analysis, analysis of the coefficient of determination, and hypothesis testing are some of the techniques utilized in data analysis. The findings of this study show that organizational culture and employee loyalty have an impact on employee performance at Am Badar & Am Badar Firms in Central Jakarta in a partial and simultaneous manner.